Effects of Fertilization and Dry-Season Irrigation on Litterfall Dynamics and Decomposition Processes in Subtropical Eucalyptus Plantations - Kong, Jiejun; Lin, Yubiao; Huang, Feng; Liu, Wenquan; He, Qian; Su, Yan; Li, Jiyue; Wang, Guangyu; Qiu, Quan (Frontiers in Ecology and Evolution, 2022)
Nutrient management in Eucalyptus plantations is critical for wood production and sustainable development. The biogeochemical mechanisms in Eucalyptus plantations are not fully understood due to changes in the spatiotemporal pattern of precipitation and plantation management. The nutrients released from litterfall are important sources of soil nutrition. We measured the seasonal production of various litterfall types and the proportions of their released nutrients in Eucalyptus urophylla × E. grandis plantations under compound fertilization, dry-season irrigation, and a combined compound fertilization and dry-season irrigation treatment. Our results showed that fertilization increased aboveground biomass and annual litterfall production (except leaf), and that the peak of litterfall production occurred in the rainy season. We found that the decomposition rates of leaf were significantly higher than that of twig, which were mainly controlled by stoichiometric characteristics, followed by soil enzyme activity (β-glucosidase, urease, and polyphenol oxidase). Fertilization decreased the carbon: nitrogen ratio and carbon: phosphorus ratio in litter, and increased soil enzyme activities, which accelerates litter decomposition and nutrient release. Dry-season irrigation increased litter decomposition and only affected the proportion of released potassium by changing the carbon: potassium ratio. Fertilization and dry-season irrigation accelerated the nutrient cycle to enhance compensatory growth. These results help to comprehend the effects of forest management on litterfall dynamics and decomposition processes in Eucalyptus plantations with seasonal drought.